Raven tales. Howl at the moon [videorecording (DVD)] (Indigenous Collection., 2017)
In this episode, the people of the village have been kept awake from the howling of the wolves, so they decide to send a party into the woods to flush them out. During the hunt, Wina becomes separated from the others in a sudden storm but he is rescued by a pair of mysterious strangers who nurse him back to health. After the storm, he reappears in the village and tells the stunned villagers about his new friends.